STUDY OF HYPOCENTER DETERMINATION AND RELOCATION, AND FOCAL MECHANISM OF MICRO EARTHQUAKES IN BANDUNG BASIN AREA - MADRINOVELLA (NIM : 22410307); pembimbing: Prof. Sri Widiyantoro, Ph.D ; Dr. Andri Dian Nugra, IKTRI
The West Java area, especially in the Bandung Basin area is surrounded by volcanic and tectonic activities, which are effected by southern Java’s subduction zone. These are proven by the earthquake occurrences in volcanoes and tectonic faults, even in micro scales (magnitude less than 2). In this thesis, we determine the hypocenter location of micro earthquakes that are recorded by seismogram of Center for Volcanology and Geological Hazard Mitigation (CVGHM) in Ciparay, Lembang, Soreang, Sumedang, Wanasuka and Tangkubanparahu. Data to be processed are some earthquakes that occurred from April to September 2011 in Bandung Basin area. The hypocenter location determination is conducted by graphic method (3 circles) and GAD method (Geiger’s method with Adaptive Damping). Then we conduct hypocenter relocation using Double Difference method (using HypoDD software) using regional velocity structure which is obtained by updating the velocity structure using Velest software. Then, we determine focal mechanism of the earthquakes using Isola software. The produced microearthquakes in the Bandung Basin area are tectonic or volcano-tectonic earthquakes, as the evidence of faults and volcanic activities in the Bandung Basin area. The results are the earthquakes with dip-slip focal mechanism (normal and thrust fault) in volcanoes area, and the earthquakes with strike-slip focal mechanism (transform fault) in active fault area.